World ocean annual mean absolute geostrophic velocity on marine geoid of EIGEN‐6C4 from WOA13. (8th June 2021) - Chu, Peter C.
Abstract: This data set was established from two open sources: (a) geoid undulation ( N ) from EIGEN‐6C4, which is a static global combined gravity field model up to degree and order 2, 190, and (b) 'World ocean geostrophic velocity inverted from World Ocean Atlas 2013 with the P‐vector method' (NCEI accession 0, 121, 576). With the given non‐positive values of N in the oceans, absolute geostrophic currents ( u, v ) are easily obtained on N with 1°×1° resolution from the second data set except the equatorial zone (5oS – 5oN) due to the non‐existence of the geostrophic balance. Altogether, the data set contains 15, 868 (u, v) data pairs. The data set shows that the hypothetical situation that there would be no flow on the geoid does not exist. Abstract : Digital data for EIGEN‐6C4 quasi‐geoid ( N* ) with 1°×1°, computed online at the website http://icgem.gfz‐potsdam.de/home